Listening to different voices - revealing local knowledge through research - Fernández, M. (Bioversity International and the International Center for Tropical Agriculture, 2016)
Maria Fernandez, Honorary Research Fellow, Bioversity International, introduces this new video, in which young scientists talk about the challenges they faced doing participatory research and how they worked creatively to overcome them.